Specific anal ulcer treatment in immunocompromised patients: A prospective study - M.A. Bocaletti-Girón; J.A. Villanueva-Herrero; B. Jiménez-Bobadilla; H.R. González-Velásquez; F. González-Jáuregui; F.G.M. Flores (Revista Médica del Hospital General de México, 2016)
Background: Specific anal ulcers occur in 11% of patients with anorectal disease. Of these, 35% present immunodeficiency with a CD4 count <500. This type of anal ulcer coexists mainly in patients who are anoreceptive, HIV positive, with haematological disorders or anal carcinoma. Objective: To determine the anal ulcer healing rate in immunocompromised patients using the three-drug regimen and/or anal ulcer excision biopsy if the first treatment fails. Materials and methods: A prospective cohort study was conducted in 32 immunocompromised patients with specific anal ulcer diagnosis. They were evaluated from January 2013 to December 2013 in the Colorectal Unit of the Hospital General de México. Patients with atypical anal ulcer were treated according to the conventional three-drug regimen: single dose of IM ceftriaxone 1 g, single dose of oral azithromycin 1 g and a 14-day course of oral acyclovir 400 mg every 6 h. Patients who did not respond as expected to the three-drug regimen were submitted to anal ulcer excision biopsy under anaesthesia. A complete anal ulcer biopsy was taken and sent to pathologist for study. The cohort was followed up for four weeks to assess healing. Though, patients who did not heal beyond this time were given a total of 6 months of follow up. Results: Healing occurred in 33% of patients who were administered the three-drug regimen. Of those patients who underwent anal biopsy, 77% had healed at 4 weeks. Those patients that did not heal had a baseline CD4 count <250. Conclusions: The cure rate for anal ulcer using the three-drug regimen is 33%, and 77% after excision biopsy.